Pro-Poor Growth: A Book Review - Seyedhossein Mirjalili (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Delivering on the Promise of Pro-Poor Growth contributes to the debate on how to accelerate poverty reduction by providing insights from eight countries that have been relatively successful in delivering pro-poor growth: Bangladesh, Brazil, Ghana, India, Indonesia, Tunisia, Uganda, and Vietnam. It integrates growth analytics with the microanalysis of household data to determine how country policies and conditions interact to reduce poverty and to spread the benefits of growth across different income groups.It is an advantage of pro-poor growth theory that instead of focusing on redistribution of income for the poor, it focuses on the pattern of economic growth and proposes participation in growth. The absolute pro-poor growth (in the Indian experience) and relative pro-poor growth (in the Bangladesh experience) have been used in this book. It is not clear how much poverty reduction should be in order to make the growth pro-poor. In addition, in this book, inclusive growth, which is a more general notion than pro-poor, is not considered. In this paper, pro-poor policies in India, centered on the eradication of absolute poverty during 1958 to 2000, have been compared with inclusive growth policies of the India's eleventh and twelfth development plans during 2007-2017.